2018
DOI: 10.1186/s12889-018-5376-y
|View full text |Cite
|
Sign up to set email alerts
|

Motivational profiles, accelerometer-derived physical activity, and acute diabetes-related symptoms in adults with type 2 diabetes

Abstract: BackgroundUsing self-determination theory, the objective of this study was to examine, over a one-month period, how physical activity (PA) motivation would influence accelerometer-derived PA behavior, and ultimately, acute diabetes-related symptoms burden among adults with type 2 diabetes (T2D adults). Using both a person and variable-centered approach, this objective was attained by means of: 1) investigating the indirect effect of PA participation on the relationship between PA motivation and acute diabetes-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
0
10
0
1
Order By: Relevance
“…Among the remaining eight studies, various factors have been reported. Specifically, BMI was positively related to fatigue (r = 0.17, p < 0.05; Castonguay & Miquelon, 2018), and females had higher fatigue than males (Kirk et al, 2015). Comorbidity was also related to fatigue.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Among the remaining eight studies, various factors have been reported. Specifically, BMI was positively related to fatigue (r = 0.17, p < 0.05; Castonguay & Miquelon, 2018), and females had higher fatigue than males (Kirk et al, 2015). Comorbidity was also related to fatigue.…”
Section: Resultsmentioning
confidence: 98%
“…Adjusting for covariates, fatigue was a significant predictor of diabetes self-care behaviors (b = −0.05, standard error = 0.02; coefficient = −0.29, p = 0.039; Kirk et al, 2015; Zhu et al, 2018). Two studies (Castonguay & Miquelon, 2018; Miquelon & Castonguay, 2016) reported that higher fatigue was associated with lower levels of physical activity motivational profiles (r = −0.16 to −0.23, p < 0.05) and actual physical activity (r = −0.16 to −0.26). Even after controlling for covariates, fatigue was a significant predictor of physical activity (Miquelon & Castonguay, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Prediction inconsistency is likely owing to complex mechanisms of self‐efficacy, perceived behavioral benefits, social environment, or motivation type that influence the transition from motivation to action 17,21,45,46 . For example, Castonguay and Miquelon analyzed the relationships among motivation types, minutes of moderate‐vigorous physical activity (MVPA), and acute diabetes‐related symptoms in a sample of 165 adults with type 2 DM 47 . Findings indicated that there was a significant indirect effect of intrinsic and extrinsic motivation to acute diabetes‐related symptoms, mediated through MVPA 47 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Castonguay and Miquelon analyzed the relationships among motivation types, minutes of moderate‐vigorous physical activity (MVPA), and acute diabetes‐related symptoms in a sample of 165 adults with type 2 DM 47 . Findings indicated that there was a significant indirect effect of intrinsic and extrinsic motivation to acute diabetes‐related symptoms, mediated through MVPA 47 . Relationships between other motivation types (eg, amotivation) and MVPA were not identified.…”
Section: Discussionmentioning
confidence: 99%
“…Nestes casos, o indivíduo tende a manifestar sentimentos positivos, como forma de evitar sentimentos negativos de indignidade, vergonha ou culpa (Gustafsson et al, 2018;Vanhalst et al, 2018). Quanto à regulação identificada, o indivíduo pode sentir-se autónomo mesmo quando externamente motivado, uma vez que este se identifica com o propósito da atividade (Castonguay & Miquelon, 2018;Haerens et al, 2018;Sheehan et al, 2018). Neste sentido, tal implica a prévia avaliação das condições contextuais de forma a avaliar a conveniência da execução da ação (Deci & Gagné, 2005;Rigby & Ryan, 2018).…”
Section: Teoria Da Autodeterminaçãounclassified